Cohort profile: The Belgian I AM frontier prospective cohort study for comprehensive health outcome exploration - Dries Heylen; Charlotte De Clerck; Murih Pusparum; Alejandro Correa Rojo; Rosette Van Den Heuvel; Geert Baggerman; Arnout Standaert; Jan Theunis; Jef Hooyberghs; Gökhan Ertaylan; Nathalie Lambrechts (PLoS ONE, 2025)
Objectives The I AM Frontier cohort was set up to support proof-of-concepts aimed at personalized prevention and health promotion. The study was designed to identify patterns, markers and processes involved in the spectrum between health and early disease onset, with the aim of generating actionable insights in a clinical setting. Study design A prospective cohort study. The study was approved by the ethics committee of the Antwerp University Hospital (RegN°: B300201938600). Methods Data collection in the I AM Frontier study spanned 12 months as a longitudinal small-scale cohort study (n = 30) conducted in the Antwerp region of Flanders, Belgium. Participants were employees of the company hosting the study, who did not have a clinical diagnosis and were between 45–60 years old. Results Even though no severe health problems were recorded at baseline, participants reported several physical complaints. There was a clear difference in longitudinal variation between clinical and research grade omics types, which might have affected their respective ability to detect intermediate molecular changes that were be linked to phenotype changes. Conclusion By integrating findings from the IAF cohort into a large-scale cohort on personalized prevention, and incorporating new technologies for microsample data collection and participant engagement, we can develop more precise and individualized health recommendations.